2013
DOI: 10.1002/mds.25298
|View full text |Cite
|
Sign up to set email alerts
|

Enteric alpha‐synuclein expression is increased in Parkinson's disease but not Alzheimer's disease

Abstract: Either PD develops selectively in the enterically α-Syn-positive population subset or PD induces this expression. Absence of increased α-Syn expression in AD points to differences in pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(116 citation statements)
references
References 38 publications
6
107
2
1
Order By: Relevance
“…Our observations are in line with Gray and colleagues, indicating that all neurologically intact subjects display αS-IR in their ganglion cell population [12]. Previous reports have reported αS-IR in none or in 8% to 82% of the neurologically intact subjects [11][12][13][14][15]. This discrepancy is related to the different antibodies used, different material assessed, i.e., surgical vs. post-mortem samples and the type of the sample, i.e., full thickness surgical sample vs. superficial endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 93%
“…Our observations are in line with Gray and colleagues, indicating that all neurologically intact subjects display αS-IR in their ganglion cell population [12]. Previous reports have reported αS-IR in none or in 8% to 82% of the neurologically intact subjects [11][12][13][14][15]. This discrepancy is related to the different antibodies used, different material assessed, i.e., surgical vs. post-mortem samples and the type of the sample, i.e., full thickness surgical sample vs. superficial endoscopic biopsy.…”
Section: Discussionsupporting
confidence: 93%
“…Each technique is specific for a particular variant or conformation of aSyn. For IHC, antibodies reactive for total (T‐aSyn‐Ab) and phosphorylated (P‐aSyn‐Ab) aSyn were selected as they have been most widely used for the detection of aSyn in the GI tract making our results comparable with these previous studies 4, 14, 15, 17, 19, 20. We also used recently developed antibodies specific for the oligomeric forms of aSyn (O‐ASN‐Abs) 26, as transformation of monomeric aSyn to oligomeric conformations is increasingly recognized as the early, key pathological event in the fibrillization process of aSyn 27.…”
Section: Introductionsupporting
confidence: 56%
“…neuritic and ganglionic ) were considered to be specifically neuronal and putatively pathological. Different antibodies showed drastically different sensitivities (and specificities) for the neuronal pattern of staining, with the highest sensitivity being achieved with the O‐aSyn‐Ab, with a positive signal in 39% of PD vs. 24% HC, followed by the P‐aSyn‐Ab with 14% of PD vs. 24% HC, and finally T‐aSyn‐Ab that surprisingly, and in contrast with other studies 4, 15, 19, 20, 33 showed no neuronal staining in any of the examined cases. We found no difference in specificity whether we used O/P‐aSyn‐Ab.…”
Section: Discussionmentioning
confidence: 67%
“…Pathological α-synuclein proteins called Lewy bodies have long been known to aggregatein the enteric nervous system (ENS) of patients diagnosed with PD and NCDLB [1][2][3][4][5][6][7][8][9][10][11][12][13]. Specifically, in PD and NCDLB, Lewy bodies appear in the myenteric plexus (MP) and the colonic submucosal plexus (CSMP) [8,[14][15][16][17][18][19][20].…”
Section: Cholinergic Lewy Pathology In the Ensmentioning
confidence: 99%
“…Increasingly, cholinergic impairments in PD and NCDLB are attributed to Lewy Body pathology (Cholinergic impairment does not appear to be a consistent finding in Alzheimer's disease (AD) [27,42]. Research consistently demonstrates that autonomic dysfunction is a feature of PD and NCDLB, but not AD and that α-synuclein expression is increased in NCDLB and PD, but not in AD [2,7,9,[43][44][45][46]. For this reason, AD is not included in this discussion) [23,28,29].…”
Section: Cholinergic Lewy Pathology In the Ensmentioning
confidence: 99%